2015
DOI: 10.5194/amt-8-4947-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the operational Aerosol Layer Height retrieval algorithm for Sentinel-5 Precursor: application to O<sub>2</sub> A band observations from GOME-2A

Abstract: Abstract. An algorithm setup for the operational Aerosol Layer Height product for TROPOMI on the Sentinel-5 Precursor mission is described and discussed, applied to GOME-2A data, and evaluated with lidar measurements. The algorithm makes a spectral fit of reflectance at the O 2 A band in the near-infrared and the fit window runs from 758 to 770 nm. The aerosol profile is parameterised by a scattering layer with constant aerosol volume extinction coefficient and aerosol single scattering albedo and with a fixed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 64 publications
1
86
0
Order By: Relevance
“…While it has been already demonstrated that a positive deviation of the true surface albedo from the assumed prior value leads to an underestimation of layer height (Sanders et al, 2015), the similar tendency of lower retrievals by GOME-2 and SCIAMACHY suggests that the influence of a wrongly prescribed aerosol model can be ruled out. This is because the KNMI/GOME-2 algorithm uses a HenyeyGreenstein phase function, whereas IUP-SCIAMACHY ingests spectrally resolved T-matrix calculations of the phase matrix representing aspherical dust particles (see Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While it has been already demonstrated that a positive deviation of the true surface albedo from the assumed prior value leads to an underestimation of layer height (Sanders et al, 2015), the similar tendency of lower retrievals by GOME-2 and SCIAMACHY suggests that the influence of a wrongly prescribed aerosol model can be ruled out. This is because the KNMI/GOME-2 algorithm uses a HenyeyGreenstein phase function, whereas IUP-SCIAMACHY ingests spectrally resolved T-matrix calculations of the phase matrix representing aspherical dust particles (see Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…While IASI is mainly sensitive to the aerosol coarse mode, SCIAMACHY and GOME-2 are sensitive to both the fine and coarse modes. The height retrieved from these sensors depends on whether the surface albedo is retrieved simultaneously or not as shown by Sanders et al (2015). They found that fixing the albedo in the retrieval gave a lower dust height than when retrieving both the albedo and the dust height.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal surface albedo database should be aerosol and cloud free, as well as representative of the viewing and solar angles encountered by the space-borne sensor. Problems related to uncertainties in surface albedo climatology for the aerosol retrieval problem are well known and were recently highlighted by Sanders et al (2015), although a different spectral band is used (O 2 −A at 758-770 nm).…”
Section: Aerosol Layer Pressure Retrievalsmentioning
confidence: 99%
“…While g = 0.7 is the reference value for most of aerosols, scenes with g = 0.6 are related to finer and weakly absorbing particles with a somewhat reduced forward scattering direction such as carbonaceous aerosols, desert dust and volcanic dash models as given by the ESA aerosol CCI project (de Leeuw et al, 2013). Values of g = 0.8 are associated with larger particles and an increased forward scattering direction such as cirrus (Sanders et al, 2015). An overestimation of g (i.e.…”
Section: Aerosol Optical Thickness Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation